Anethole exerted anticonvulsant effect in pentylenetetrazolemodel of seizure in male mice: Possible antioxidant effects - Sanaz Salimian; Saeid Habibian-Dehkordi; Jahangir Kaboutari; Hossein Amini-Khoei; Mohammad Sajad Barkhordari (Shahrekord University of Medical Sciences, 2022)
Background and aims: Epilepsy is a neurological disorder causing brain dysfunctions. Treatment and control of epilepsy have long been a challenge in medical sciences. Despite the variety of current anticonvulsant drugs, research continues to discover new drugs with the highest efficacy and the lowest side effects. In the present study, the anticonvulsant effects of anethole in the seizure induction with pentylenetetrazole (PTZ) were evaluated in a mice model with respect to its possible antioxidant effects. PTZ is known to cause generalized epilepsy in animal models.Methods: Accordingly, in this experimental study, 40 mice were divided into 5 groups; the first group received normal saline, the second group received 10 mg/kg diazepam, and the third to fifth groups were given anethole at 31.25, 62.5 and 125 mg/kg, respectively. Injections were conducted intraperitoneally for one week; then seizures were induced by the intravenous injection of 90 mg/kg PTZ. After determination of the duration of seizures in different groups, the mice were finally placed under deep anesthesia and their prefrontal cortex tissue was isolated to measure nitric oxide (NO), antioxidant capacity and malondialdehyde (MDA) concentrations.Results: The results showed that anethole increased the delay in the onset of seizures, decreased the amount of nitrite in the brain, enhanced antioxidant capacity, and reduced MDA content in a dose-dependent manner.Conclusion: Overall, our results indicated the anticonvulsant effects of anethole that could be mediated by inhibiting oxidative stress.